EMOTIONAL GEOGRAPHY OF A PRE-SERVICE ENGLISH TEACHER IN ONLINE TEACHING PRACTICUM DURING COVID-19 PANDEMIC - Ninik Tri Astutik; Astri Hapsari (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2022)
Due to COVID-19 pandemic, online learning has now become a bridge to facilitate teaching practice. Emotion has received little attention in online learning and online teaching practice for a senior high school, particularly for pre-service teachers. The study attempted to investigate a pre-service teacher's emotion during her online teaching practicum by using Hargreaves's (2001) concept of emotional geography. The data were gathered from diary journals and interviews conducted over the course of a month of teaching practice in a senior high school. The narratives were analysed using a descriptive qualitative approach combined with thematic analysis. The findings show that the pre-service English teacher experienced a variety of positive and negative emotions because of understanding and misunderstanding in schools, and that these emotions gradually changed her perceptions of her teaching practice. This research offers a novelty in terms of describing how a pre-service English teacher adapted from offline to online teaching practice utilizing WhatsApp Group and Google Classroom to share materials and deliver assessments at the time of COVID-19 pandemic. Emotional resilience and good communication skills were proven to help the participant in navigating emotional geography in online teaching practice with limited faceto-face interaction and guidance with the teacher supervisor in the school.